IMPROVING THE EFFECTIVENESS OF STUDENT INDEPENDENT WORK BY INTODUCTION OF CLOUD STORAGE TECHNOLOGY - Alexandr A. Isaev; Tatiana M. Plekhanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
IMPROVING THE EFFECTIVENESS OF STUDENT INDEPENDENT WORK BY INTRODUCTION OF CLOUD STORAGE TECHNOLOGY